Active OB stars : structure, evolution, mass-loss, and critical limits : proceedings of the 272nd symposium of the International Astronomical Union held in Paris, France, July 19-23, 2010 - International Astronomical Union. Symposium 2010 : Paris, France); Neiner, C. (Coralie) (Cambridge, UK ; New York : Cambridge University Press, 2011)
IAU Symposium 272 presents an overview of the latest research into active OB stars. These massive, volatile objects serve as test beds for extreme conditions, and research into them has entered a new era with the advent of new space and round-based instrumentation. In this volume, renowned experts discuss the cutting-edge observations, state-of-the-art modeling and recently developed techniques such as asteroseismology, interferometry and spectropolarimetry that have improved our understanding of these extreme objects. Asteroseismology allows us to infer the internal structure of massive stars and their rotation; high-resolution spectropolarimetry provides clues about magnetic fields and the confinement of their circumstellar environments; and interferometry probes the shape of these environments and investigates differential rotation. Written for researchers and graduate students, this volume will appeal to all those interested in extreme physical processes as tools to study structure evolution and mass loss of active OB stars. -- Back cover.
Part I. Opening the symposium --- Part II. Rapid rotation and mixing in active OB stars --- Part III. Winds and magnetic fields of active OB stars --- Part IV. Populations of OB stars in galaxies --- Part V. Circumstellar environment of active OB stars --- Part VI. Periodic variations and asteroseismology of OB stars --- Part VII. 'Normal' and active OB stars as extreme condition test beds --- Part VIII. Last Minute Contribution --- Part IX. Closing the symposium.
Includes bibliographical references and indexes.
Keywords: O stars -- Congresses; B stars -- Congresses; Early stars -- Congresses